Household electrical appliances: a comparative study between laws of Malaysia and the United States / Anis Aqilah Ahmad Zubir … [et al.] - Ahmad Zubir, Anis Aqilah; Abdul Rahim, Rosliza; Zulkifli, Siti Nurzakirah; Fikri Abazah, Syafiqah (2014)
The purpose of this research is to study the strengths and weaknesses of Consumer Protection Act 1999 (CPA) in terms of product safety, specifically on the safety standards for household electrical appliances in Malaysia. This research is important because there are certain products that pose danger and harm to consumers but are, nevertheless, readily available in the Malaysian market. Statistics on injuries caused by household electrical appliances are cited as evidence of this. For a product to be released, it must be safe, without any defects and are not harmful or dangerous to consumers. This study mainly focuses on the CPA 1999 and the Consumer Product Safety Act 1972 of the United States. It also looks at various rules and safety standards in both Malaysian and the US. Comparisons are made to ascertain the strengths and weaknesses of Malaysian law and position. This study is divided into six parts, namely, the safety standards, agencies or authorities that deal with product safety, export and import of the products, penalties, enforcement and lastly consumers' access to information. At the end of the study, recommendations are made in order to strengthen Malaysian law on the safety of household electrical appliances.